Growth and senescence of mavuno, marandu, ipyporã and mulato II grasses subjected to stockpiling - Bruno Humberto Rezende Carvalho; Gustavo Segatto Borges; Dallety Haloma Alves Miler de Oliveira; Geovana Lopes Nascimento; Khazuê Ubagai Machado; Manoel Eduardo Rosalino Santos (Ciência Animal Brasileira)
The objective of this study was to evaluate, during the stockpiling period, the growth and senescence of marandu, mavuno, ipyporã and mulato II grasses. The experimental design was completely randomized, with four replications. The experiment was repeated in 2 years (2020 and 2021). The leaf appearance (LApR) and elongation rate (LElR), stem elongation rate, tiller population density, growth rates at canopy level, as well as canopy leaf senescence rate showed higher values at the beginning in relation to the end of the stockpiling period. The leaf life span showed an inverse response pattern. Among the cultivars, mavuno grass presented the highest LApR and total canopy growth rate. The LElR and canopy leaf growth rate were higher in mavuno and marandu grasses than in mulato II and ipyporã grasses. The stem elongation rate was higher in mavuno and ipyporã grasses compared to mulatto II and marandu grasses. In general, the growth rate of individual tillers and canopy during the stockpiling period decreased in the following sequence: mavuno grass > marandu grass > ipyporã grass > mulatto II grass.